Criminalistics characteristics of arms trafficking offences committed by organised groups and criminal organisations - R. E. Veliiev (Bulletin of Kharkiv National University of Internal Affairs)
The article identifies which criminal offences fall into the category of those related to illicit arms trafficking and are the most common in the recorded proportion of criminal offences committed by organised groups and criminal organisations. These include, in particular, criminal offences under Articles 201, 262, 263, 263-1, 264, 410, 411 of the Criminal Code of Ukraine. The author also emphasises the need to include here also those crimes provided for in Articles 269 and 440 of the Criminal Code of Ukraine, but given that they are not common in the recorded number of crimes and criminal offences, it is justified that it is inexpedient to study them in depth.